Joint Action to Prevent Stunting and Obesity in the Tanah Kali Kedinding Health Center, Kenjeran District, Surabaya - Riezky Faisal Nugroho; Mujayanto Mujayanto; Nuning Marina Pengge; Nurul Hindaryani; Erlyna Jayeng Wijayanti; Erika Martining Wardani (Universitas Muhammadiyah Purworejo, 2022)
Stunting in children is a serious problem because it is associated with the risk of future illness and the difficulty of achieving optimal physical and cognitive development. The prevalence of stunting in Surabaya is found in several working areas of the puskesmas, one of which is at the Tanah Kali Kedinding Health Center at 25.37%. Obesity is a condition in which the accumulation of excess or abnormal fat is bad for health. The World Health Organization (WHO) in 2014 noted that 1.9 billion adults were overweight with a prevalence of 39% having children under five were overweight and obese. The case of obesity in the city of Surabaya itself ranks second highest in East Java Province, which is as many as 98,344 cases. This activity aims to increase knowledge about stunting and obesity prevention for pregnant women and mothers under five. This service method uses increasing knowledge about stunting and obesity in everyday life for pregnant women and mothers of toddlers, measuring nutritional status in Toddlers and cooking demonstrations of healthy snacks using the Risoles menu of Tongkol Ragout Fresh Bread. The results obtained, namely pregnant women and mothers under five experienced an increase in knowledge about stunting and obesity respectively 80% and 82%, both of which were classified as good.